Fenomena Pola Pengeluaran Ekonomi Mahasiswa FISH yang Tinggal di Kost di Jalan Daksinapati, Pemuda dan Rawamangun Muka - Rafi Adrian Syahputra; Vivi Widiyaningsih; Zihad Ahmad Alfarraby; Asep Suryana; Rusfadia Saktiyanti Jahja (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
The phenomenon of the economic spending patterns of FISH students at Jakarta State University living in the Daksinapati, Pemuda, and Rawamangun Muka areas reflects the socio-economic dynamics of out-of-town students adjusting to independent living in a big city. This study employed a qualitative descriptive approach through in-depth interviews with five informants living in three different boarding houses. The analysis was conducted using Mark Granovetter's (1985) Embeddedness theory, which emphasizes that individual economic actions are always embedded within social networks, norms, and interpersonal relationships that shape their consumption decisions. The results show that student spending is influenced not only by primary needs such as rent, food, and transportation, but also by social relationships within the boarding house and campus, which give rise to latent expenditures such as hanging out, pooling activities, organizational solidarity, and peer lifestyle demands. Thus, the consumption patterns of out-of-town students are not merely individual economic activities but also social mechanisms reflecting the process of adaptation, solidarity, and efforts to maintain integration within the social environment they inhabit.